2011
DOI: 10.1017/s1751731111000917
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in wholesale carcass cuts predicted from digital images in cattle

Abstract: The objective of this study was to quantify the genetic variation in carcass cuts predicted using digital image analysis in commercial cross-bred cattle. The data set comprised 38 404 steers and 14 318 heifers from commercial Irish herds. The traits investigated included the weights of lower value cuts (LVC), medium value cuts (MVC), high value cuts (HVC), very high value cuts (VHVC) and total meat weight. In addition, the weights of total fat and total bones were available on the steers. Heritability of carca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
30
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 15 publications
9
30
1
1
Order By: Relevance
“…The moderate heritability estimates in the present study for the nonreproduction traits agree within international estimates for live weight (Koots et al, 1994;Phocas and Sapa, 2004), carcass traits (Koots et al, 1994;Marshall, 1994;Hoque et al, 2006), and type traits (Koots et al, 1994;Gutiérrez et al, 2002;Bouquet et al, 2010) and have been discussed in detail elsewhere for Irish cattle (McHugh et al, 2010Pabiou et al, 2011) using data similar to that used in the present study.…”
Section: Population Statistics and Heritability Estimatessupporting
confidence: 88%
See 1 more Smart Citation
“…The moderate heritability estimates in the present study for the nonreproduction traits agree within international estimates for live weight (Koots et al, 1994;Phocas and Sapa, 2004), carcass traits (Koots et al, 1994;Marshall, 1994;Hoque et al, 2006), and type traits (Koots et al, 1994;Gutiérrez et al, 2002;Bouquet et al, 2010) and have been discussed in detail elsewhere for Irish cattle (McHugh et al, 2010Pabiou et al, 2011) using data similar to that used in the present study.…”
Section: Population Statistics and Heritability Estimatessupporting
confidence: 88%
“…With the exception of producer scored animal quality and docility, the fixed effects included in the models for the other traits have been described elsewhere (Crowley et al, 2010;McHugh et al, 2011;Pabiou et al, 2011). Contemporary group or groups was included in the model as a fixed effect for all traits and gender was included when more than one gender was included in the analysis but not implicitly assumed within the definition of contemporary group.…”
Section: Estimation Of Genetic Parametersmentioning
confidence: 99%
“…Carcass weight, which reflects lifetime growth, is a routinely evaluated trait in many beef genetic evaluations (Pabiou et al, 2011b). The genetic parameter estimates obtained in the present study using RRM corroborate those reported in other cattle populations estimated using traditional linear models (Gregory et al, 1995;Kause et al, 2015), including those from data on Irish cattle (Hickey et al, 2007;Pabiou et al, 2009Pabiou et al, , 2011a. The average heritability for carcass weight across genders and age at slaughter in the present study (0.23 ± 0.01) is similar to the estimate reported by Hickey et al (2007) in Irish beef cattle, estimated using a linear animal model with a phenotypic adjustment for age.…”
Section: Genetic Parameters For Carcass Weightsupporting
confidence: 83%
“…Although RRM previously have been used to model animal weight (live weight) in cattle (Meyer, 2000;Coffey et al, 2006), the use of RRM to model animal conformation or fat are nonexistent in beef cattle, although it has been undertaken in dairy cattle (Coffey et al, 2001). As with carcass weight, the heritability estimates for conformation and fat score were within the ranges of those reported from traditional linear models in other international beef populations (Utrera and Van Vleck, 2004) and in Irish populations (Hickey et al, 2007;Crowley et al, 2011;Pabiou et al, 2011a). Pabiou et al (2011a), using data from Irish abattoirs, reported direct heritability estimates for conformation and fat score ranging from 0.28 to 0.46 and from 0.27 and 0.40, respectively, from an animal linear mixed model.…”
Section: Genetic Parameters For Carcass Conformation and Fatmentioning
confidence: 66%
See 1 more Smart Citation